2013
DOI: 10.4187/respcare.02452
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Exercise-Induced Oxygen Desaturation in Systemic Sclerosis Patients With Interstitial Lung Disease

Abstract: BACKGROUND:The diffusion capacity of the lung for carbon monoxide (D LCO ) is a good marker of disease severity in patients with idiopathic interstitial pneumonia, and is associated with oxygen saturation; however, little is known about D LCO in systemic sclerosis patients with interstitial lung disease. We studied potential predictors of exercise-induced oxygen desaturation in patients with systemic sclerosis. METHODS: Data were collected prospectively from 80 of 110 consecutive systemic sclerosis patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…reduced predicted lung volumes seem to predict oxygen desaturation in exercise testing (Someya et al, 2014). PAH and exercise-induced PAH are common features in SSc (Gargani et al, 2013;Saggar et al, 2010;Suzuki et al, 2015;Voilliot et al, 2014).…”
Section: Reduced Diffusion Lung Capacity For Carbon Monoxide (Dlco) Andmentioning
confidence: 87%
See 1 more Smart Citation
“…reduced predicted lung volumes seem to predict oxygen desaturation in exercise testing (Someya et al, 2014). PAH and exercise-induced PAH are common features in SSc (Gargani et al, 2013;Saggar et al, 2010;Suzuki et al, 2015;Voilliot et al, 2014).…”
Section: Reduced Diffusion Lung Capacity For Carbon Monoxide (Dlco) Andmentioning
confidence: 87%
“…Exercise‐induced oxygen desaturation may occur in patients with SSc and ILD (Someya, Mugii, Hasegawa, Yahata, & Nakagawa, ). Reduced diffusion lung capacity for carbon monoxide (DLCO) and reduced predicted lung volumes seem to predict oxygen desaturation in exercise testing (Someya et al, ). PAH and exercise‐induced PAH are common features in SSc (Gargani et al, ; Saggar et al, ; Suzuki et al, ; Voilliot et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in SpO 2 to ≤88% during 6MWT predicts a high-mortality risk in patients with IPF (37). A factor underlying exercise-induced oxygen desaturation may be reduced as %DLco, which was found to be useful as a predictor in more than 80% of subjects (22).…”
Section: Evaluation Indices For Rehabilitation For Sscmentioning
confidence: 99%
“… 13 Peripheral muscle dysfunction is an essential contributor to reduced exercise capacity in ILD patients, and the resulting reduction in activity leads to a vicious cycle that exacerbates exercise capacity and dyspnea. 14 16 In addition, it has been reported that oxygen supplementation in IPF patients improves cerebral and muscle oxygenation and alleviates dyspnea. 17 From this perspective, we considered oxygenation of the quadriceps, which is the most important muscle for walking, as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%